Structure and function of pectic enzymes: Virulence factors of plant pathogens - Herron, Steven R. (The National Academy of Sciences, 2000)
The structure and function of Erwinia chrysanthemi pectate lysase C, a plant virulence factor, is reviewed to illustrate one mechanism of pathogenesis at the molecular level. Current investigative topics are discussed in this paper.